2008
DOI: 10.1080/10400410802060059
|View full text |Cite
|
Sign up to set email alerts
|

Images of Resistance: A Qualitative Enquiry Into the Meanings of Personal Artwork for Women Living With Cancer

Abstract: This study explored the meanings, inspirations and subjective significance of personal artwork created as a leisure activity by women living with cancer. A convenience sample of twelve women aged between 23-74 years participated in semi-structured interviews. Participants were living in various stages of the cancer trajectory, and engaged in several forms of visual art-making. They submitted examples of their artwork by photograph and then participated in semi-structured interviews. From a phenomenological ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…The perceptions shown in qualitative or mixed-methods research could not be revealed by quantitative methodologies. As a case in point, Reynolds and his colleagues (i.e., Reynolds, 2003Reynolds, , 2004Reynolds, Lim, & Prior, 2008) interpreted personal experiences of women living with cancer and other 434 LONG chronic illnesses when they were creating artwork as leisure. The focuses of these studies were on meanings, inspirations, and subjective significance shown in the process of making the artwork, which cannot be comprehended only by using questionnaires and universally defined constructs.…”
Section: Discussionmentioning
confidence: 99%
“…The perceptions shown in qualitative or mixed-methods research could not be revealed by quantitative methodologies. As a case in point, Reynolds and his colleagues (i.e., Reynolds, 2003Reynolds, , 2004Reynolds, Lim, & Prior, 2008) interpreted personal experiences of women living with cancer and other 434 LONG chronic illnesses when they were creating artwork as leisure. The focuses of these studies were on meanings, inspirations, and subjective significance shown in the process of making the artwork, which cannot be comprehended only by using questionnaires and universally defined constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Self-esteem has been shown to be an effective buffer against stress (e.g., [10,22]), implicated in coping with chronic illness [23], and to support well-being [1], positive affect in chronic disease patients [22] and mental health [24]. Meaning in life, in particular, has been strongly associated with coping and mental health [12,13,[25][26][27][28][29][30][31][32].…”
Section: How Does the Tcm-r Work?mentioning
confidence: 99%
“…At the interface of this connection lies the opportunity for positive transformation and personal growth [3,11]. Creativity [12] and spirituality [13] are both a search for the sacred, with creativity also being a search for the self [10]. Both creativity [11] and spirituality [14] have transformative power and are a quest for meaning and unity [3].…”
Section: The Transformative Coping Model (Tcm-r)mentioning
confidence: 99%
“…Studies exploring professional or amateur artists' experiences of therapeutic processes in artmaking (Reynolds, 2000(Reynolds, , 2010Reynolds & Lim, 2007;Reynolds, Lim & Prior, 2008) were conducted in recreational, educational, artistic or hobby settings rather than art therapy contexts. However, the participants in these studies suffered from somatic or psychic chronic illnesses, so the studies can be categorised as exploring the impacts experienced of art as therapy.…”
Section: Overview Of Clients' Experiences Of Helpful and Hindering Prmentioning
confidence: 99%